The leadership practices of the Multinational Company in China - ZHIZHUO, XU (2017)
The emergence of global economy gives rise to the research interest in individuals with cross-cultural background. As the study of leadership development has never stopped in recent decades, the author explores the differences between leadership of multinational companies in China and that in the companies of other forms. In the first part, the author reviews some related studies, especially some basic theories about leadership to show leaders are playing an important role in the organisation, and then analyses the current market of international business especially the globalization in China. In Methodology part, the author uses a qualitative method named semi-structured interview to collect primary data. This study selects 20 interviewees from a US-funded company located in China. The third part is data analysis and findings from the interviews. The importance of a successful organisational culture is discussed as they will influence the leadership style and the desire of leadership development. In the end, some limitations of this paper are presented, such as the small quantity of samples and the lack of practical solutions to leadership development. Some findings are got in this study. Firstly, those leaders who are skilful in some specific fields pay little attention to leadership development may be more interested in improving their professional abilities, as result, they ignore the development of leadership. Secondly, leaders who think highly of leadership will more often focus on how to develop their followers rather than their self-improvement. In addition, the author finds out the root cause of these findings is the different leaders’ attitudes towards their leadership.